DIFFERENTIAL EXPRESSION OF STROMA DERIVED FACTOR-1 ISOFORMS IN BLADDER CANCER - Gosalbez, Miguel (2013)
PURPOSE: Stroma-Derived Factor (SDF)-1 is a ligand for chemokine receptors CXCR4 and CXCR7. The six known SDF-1 isoforms are generated by alternative mRNA splicing. While SDF-1 expression has been detected in various malignancies, only a few studies have reported differential expression of SDF-1 isoforms and its clinical significance. In this study we evaluated the expression three SDF-1 isoforms (α,β,γ) in bladder cancer (BCa). METHODS: Using quantitative PCR, mRNA levels of SDF-1α, SDF-1β and SDF-1γ were measured in bladder tissues (normal: 25; BCa: 44) and urine specimens (n=210; normal: 28; benign conditions: 74; BCa: 57, history of BCa (HxBCa): 35, Hx other Ca: 8; other Ca: 8) from consecutive patients. These levels were correlated with clinical outcome. RESULTS: Among SDF-1 isoforms, only SDF-1β mRNA was significantly overexpressed by 2.5-6-fold in BCa tissues when compared to normal bladder tissues. While SDF-1α was expressed in bladder tissues, SDF-1γ expression was undetectable. In multivariate analysis, SDF-1β (P=0.017) was an independent predictor of metastasis and disease specific mortality (P=0.043). In exfoliated urothelial cells, only SDF-1β mRNA levels were differentially expressed and having a 91.2% sensitivity and 73.8% specificity for detecting BCa. In patients with HxBCa, elevated SDF-1β levels indicated 4.3-fold increased risk (P=0.0001) for developing recurrence within 6-months. CONCLUSION: SDF-1 isoforms are differentially expressed in bladder tissues and exfoliated urothelial cells. SDF-1β mRNA levels in BCa tissues predict poor prognosis. Further, SDF-1β mRNA levels in exfoliated cells detect BCa with high sensitivity and are potential predictors of future recurrence.